Si-Al nanospheres for the valorization of galactose and agarose into 5-hydroxymethylfurfural. - Torres-Olea, Benjamín; Rodríguez Carballo, Gabriela; García-Sancho, Cristina; Moreno-Tost, Ramón; Cecilia-Buenestado, Juan Antonio; Maireles-Torres, Pedro Jesús (My University, 2023)
5-hydroxymethylfurfural (HMF) is a compound that has gained attention to potentially substitute fossil resources in areas such as the polymer industry or the production of energy vectors. HMF is produced from the acid treatment of hexoses, such as glucose or galactose. In this sense, algae biomass has gained interest as it can be grown in both, sweet and salt water and their growth rate and CO2 fixation are several times higher than those of terrestrial plants. Red algae, which are rich in agarose, a galactose and 1,6-dehydrogalactose heteropolymer, can potentially be used as feedstock to produce HMF [1]. Hence, in this work, alumina supported nanospheres have been synthetised and employed as acid catalysts due to their high acidity and porosity that allows the selective conversion of these biomass derived compounds into valuable HMF.
Keywords: Glúcidos - Aplicaciones industriales; Galactosa - Aplicaciones industriales; Agarosa - Aplicaciones industriales; Catálisis heterogénea; 5-hidroximetilfurfural; Agarosa; Galactosa; Deshidratación